Can Cardiopulmonary Rehabilitation Facilitate Weaning of Extracorporeal Membrane Oxygenation (CaRe-ECMO)? Study Protocol for a Prospective Multidisciplinary Randomized Controlled Trial - Zheng, Yu; Sun, Hao; Mei, Yong; Gao, Yongxia; Lv, Jinru; Pan, Dijia; Wang, Lu; Zhang, Xintong; Hu, Deliang; Sun, Feng; Li, Wei; Zhang, Gang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Mortality of patients suffering from critical illness has been dramatically improved with advanced technological development of extracorporeal membrane oxygenation (ECMO) therapy. However, the majority of ECMO-supported patients failed to wean from ECMO therapy. As one of several options, cardiopulmonary rehabilitation serves as effective intervention in the improvement of cardiovascular and respiratory function in various major critical illness. Nonetheless, its role in facilitating ECMO weaning has not yet been explored. The purpose of this study is to investigate the effectiveness of cardiopulmonary rehabilitation on rate of ready for ECMO weaning in ECMO-supported patients (CaRe-ECMO). Methods: The CaRe-ECMO trial is a randomized controlled, parallel group, clinical trial. This trial will be performed in a minimum number of 366 ECMO-supported eligible patients. Patients will be randomly assigned to either: (1) the CaRe-ECMO group, which will be treated with usual care including pharmacotherapy, non-pharmacotherapy, and specific nursing for ECMO therapy and the CaRe-ECMO program; or (2) the control group, which will receive usual care only. The CaRe-ECMO program consists of protocolized positioning, passive range of motion (PROM) training, neuromuscular electrical stimulation (NMES), surface electrical phrenic nerve stimulation (SEPNS), and pulmonary rehabilitation. The primary outcome of the CaRe-ECMO trial is the rate of ready for ECMO weaning at CaRe-ECMO day 7 (refers to 7 days after the CaRe-ECMO program initiation). Secondary outcomes include rate of ECMO and mechanical ventilation weaning, total length in day of ready for ECMO weaning, ECMO weaning and mechanical ventilation, all-cause mortality, rate of major post-ECMO complications, ECMO unit length of stay (LOS) and hospital LOS, total cost for hospitalization, cerebral performance category (CPC), activities of daily living (ADL), and health-related quality of life (HRQoL). Discussion: The CaRe-ECMO is designed to answer the question “whether cardiopulmonary rehabilitation can facilitate weaning of ECMO (CaRe-ECMO).” Should the implementation of the CaRe-ECMO program result in superior primary and secondary outcomes as compared to the controls, specifically the add-on effects of cardiopulmonary rehabilitation to the routine ECMO practice for facilitating successful weaning, the CaRe-ECMO trial will offer an innovative treatment option for ECMO-supported patients and meaningfully impact on the standard care in ECMO therapy. Clinical Trial Registration:ClinicalTrials.gov, identifier: NCT05035797.